2022
DOI: 10.1002/jimd.12562
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of infantile nephropathic cystinosis depends on early intervention, not genotype: A multicenter sibling cohort study

Abstract: Infantile nephropathic cystinosis (INC) is an inheritable lysosomal storage disorder characterized by lysosomal cystine accumulation, progressive kidney disease, and multiple extrarenal complications (ERCs). Cysteamine postpones the onset of end-stage kidney disease (ESKD) and reduces the incidence of ERCs; however, cysteamine is generally initiated upon establishment of the renal Fanconi syndrome (FS) and partial loss of kidney function, whereas data Koenraad Veys and Ward Zadora contributed equally to this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For example, neonatal screening is now considered one of the most efficient strategies to identify the disease and initiate treatment as early as possible, which could delay the onset of kidney failure and provide optimized care for NC patients. A recent study from Germany showed that starting cysteamine soon after birth yielded almost normal growth and kidney function in these patients with a neonatal diagnosis [ 30 , 31 ]. Still, the availability of such strategies in low-income countries is questionable, let alone access to potential innovative therapies such as stem cell transplantation [ 32 ], or inflammation-targeted therapies [ 33 ], which are very likely to be available only in a restricted number of DEed countries.…”
Section: Discussionmentioning
confidence: 99%
“…For example, neonatal screening is now considered one of the most efficient strategies to identify the disease and initiate treatment as early as possible, which could delay the onset of kidney failure and provide optimized care for NC patients. A recent study from Germany showed that starting cysteamine soon after birth yielded almost normal growth and kidney function in these patients with a neonatal diagnosis [ 30 , 31 ]. Still, the availability of such strategies in low-income countries is questionable, let alone access to potential innovative therapies such as stem cell transplantation [ 32 ], or inflammation-targeted therapies [ 33 ], which are very likely to be available only in a restricted number of DEed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this analysis considers patients diagnosed from birth and initiating treatment shortly thereafter (i.e., before the age of 5). However, there is evidence to show an independent and significant positive relationship between age at treatment initiation and kidney and overall survival [ 8 , 17 , 24 ]. Therefore, this analysis could be extended such that results are stratified not only by compliance levels but also by age at treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, considering the top 10% of CCSs (i.e., the most compliant patients) assessed in Nesterova et al (2015), the mean age-at-KF observed was approximately 23 years [ 13 ]. Although Nesterova et al (2015) do not make explicit the age at treatment initiation for these patients, it is likely these patients started treatment early; recent data from Emma et al (2021) make clear that age at renal failure (defined as stage 5 chronic kidney disease) is significantly associated with age at treatment initiation [ 17 , 24 ]. Furthermore, Emma et al (2021) also shows a median age of approximately 18 years before renal failure for patients with a mean leucocyte cystine level between 1.2 and 1.8 nmols, irrespective of age at initiation or treatment duration [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, a strict dosing schedule and accurate therapeutic follow-up is required [ 4 ]. Cysteamine should be administered immediately upon the diagnosis of nephropathic cystinosis, as any delay in treatment negatively impacts long-term renal outcome [ 11 , 12 ]. Patients with ocular cystinosis do not require systemic cysteamine, and their treatment is limited to focal cysteamine eye drops to treat corneal cystine crystals.…”
Section: Introductionmentioning
confidence: 99%